Homoclinic orbits for second order nonlinear p-Laplacian difference equations - X. Deng; X. Liu; H. Shi; T. Zhou (Հայաստանի ԳԱԱ)
The paper proves the existence of nontrivial homoclinic orbits for second order nonlinear p-Laplacian difference equations without on assumptions on pereodicity using the critical point theory. Moreover, if the nonlinearity is an odd function, the existence of an unbounded sequence of nontrivial homoclinic orbits is proved.
Keywords: Science; Mathematics